Financial knowledge and financial behaviour influence on personal financial distress among undergraduate students of public universities in Malaysia / Nelson Lajuni - Lajuni, Nelson (Institute of Graduate Studies, UiTM, 2018)
The issues of financial mismanagement among youths have been growing at an alarming rate lately as reported by The Malay Mail in 2016 that on average eleven youths declared bankrupt every day. As such, immediate remedial measures need to be identified on whether the role of financial socialization and the influence of financial knowledge and the change in financial behaviour may lead to the solution to this problem. Therefore, the motivation of this doctoral dissertation is to examine the influence of financial knowledge and financial behaviour towards personal financial distress of undergraduates in Malaysia. The first step involves reviewing the body of literature on financial distress to identify useful models and concepts. The paucity of reference to financial distress in that literature is eminent, especially here in Malaysia in which the discussion focuses on issues related to financial distress faced by undergraduates in Malaysia…